2014
DOI: 10.1038/ismej.2014.165
|View full text |Cite
|
Sign up to set email alerts
|

Host adaptive immunity alters gut microbiota

Abstract: It has long been recognized that the mammalian gut microbiota has a role in the development and activation of the host immune system. Much less is known on how host immunity regulates the gut microbiota. Here we investigated the role of adaptive immunity on the mouse distal gut microbial composition by sequencing 16 S rRNA genes from microbiota of immunodeficient Rag1 À / À mice, versus wild-type mice, under the same housing environment. To detect possible interactions among immunological status, age and varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(175 citation statements)
references
References 61 publications
8
156
2
1
Order By: Relevance
“…Based on analysis of all samples across all time points, α-diversity was higher and β-diversity was lower in M. vaccae-immunized mice compared with vehicle-immunized mice (Fig. S4 A-E) [LMM, α-diversity, M. vaccae, phylogenetic diversity, F (1, 26.9) = 5.9, P < 0.05; observed species, F (1, 31.1) = 5.4, P < 0.05; Shannon index, F (1, 37.0) = 11.8, P < 0.01; M. vaccae × CSC × day, phylogenetic diversity, F (16, 36.1) = 2.1, P < 0.05; observed species, F (16, 36.1) = 2.1, P < 0.05; Shannon index, F (16, 47.5) = 1.3, P = 0.27], indicating that M. vaccae immunization had a stabilizing effect on the gut microbiota throughout the study, consistent with recent studies demonstrating that host adaptive immunity modulates the gut microbiota (40). In line with these findings, multiple linear regression showed that 11% of the variation in the gut microbiota was explained by the histological damage score in the colon, reflecting intestinal immune activation.…”
Section: Persistent Effects Of M Vaccae Immunization On Brain Serotosupporting
confidence: 75%
“…Based on analysis of all samples across all time points, α-diversity was higher and β-diversity was lower in M. vaccae-immunized mice compared with vehicle-immunized mice (Fig. S4 A-E) [LMM, α-diversity, M. vaccae, phylogenetic diversity, F (1, 26.9) = 5.9, P < 0.05; observed species, F (1, 31.1) = 5.4, P < 0.05; Shannon index, F (1, 37.0) = 11.8, P < 0.01; M. vaccae × CSC × day, phylogenetic diversity, F (16, 36.1) = 2.1, P < 0.05; observed species, F (16, 36.1) = 2.1, P < 0.05; Shannon index, F (16, 47.5) = 1.3, P = 0.27], indicating that M. vaccae immunization had a stabilizing effect on the gut microbiota throughout the study, consistent with recent studies demonstrating that host adaptive immunity modulates the gut microbiota (40). In line with these findings, multiple linear regression showed that 11% of the variation in the gut microbiota was explained by the histological damage score in the colon, reflecting intestinal immune activation.…”
Section: Persistent Effects Of M Vaccae Immunization On Brain Serotosupporting
confidence: 75%
“…These taxa-specific responses to perturbation by HPA axis activity could be due to attenuation of adaptive immunity, which, unlike innate immunity, is a non-general response [23,26]. Therefore, taxa suppressed by an adaptive immune response would be expected to increase in abundance following heightened HPA axis activity.…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal IgA is one such immune component that preferentially targets colitogenic members of the microbiota, including SFB and A. muciniphila (34,39,41,56,57). Reciprocally, certain pathobionts can produce proteolytic enzymes that degrade intestinal IgA and thereby enhance colitis susceptibility (40).…”
Section: Discussionmentioning
confidence: 99%